Peran Bimbingan Konseling Terhadap Self Managemen Peserta didik dalam Belajar - Reza Hawari; Nur Ainun Damanik; Linda Linda; Gusman Lesmana (Universitas Muhammadiyah Enrekang, 2023)
Every learner wants to have the ability to manage their time, especially in learning. Self-management in learning is one type of problem that arises in students. Self-management is a technique that leads to individual thoughts and behaviors to regulate and change for the better through the process of learning new behaviors. Tutoring is one of the fields of guidance, to examine the understanding of tutoring, it will first be discussed about the nature of guidance itself. This research approach is descriptive qualitative. This study aims to determine the role of counseling guidance on self-management of students in learning. These behavioral and mental changes will have a destructive impact on the development of students, if they do not get the right assistance. Guidance and Counseling teachers are expected to play a role in anticipating the impact of changes in learning patterns experienced by students and provide appropriate assistance.